MADRASAH HEAD STRATEGY IN DEVELOPING TEACHER PROFESSIONAL COMPETENCE AT MADRASA ALIYAH SIRNAMISKIN BANDUNG - Muchtarom Muchtarom (Sekolah Tinggi Agama Islam Al Hidayah, 2022)
The purpose of this study is to find out the following: Teacher Professional Competence at MAN 1 Bandung. Knowing the strategy for developing teacher professional competence, the constraints of the madrasa head in developing teacher professional competence. The research method used with a descriptive qualitative approach, can interpret the existing data. Data collection techniques were in the form of observation, interviews, and documentation studies with an emphasis on sources from informants: Madrasah Heads, Deputy Madrasah Heads for Curriculum, and Teachers to confirm the validity of the data obtained. The results of the study are (1) Teacher Professional Competency at Madrasa Aliyah Sirnamiskin Bandung, (2) Strategy of Madrasa Heads in Developing Teacher Professional Competence at Madrasa Aliyah Sirnamiskin Bandung. (3). Obstacles faced by madrasa heads in developing teacher professional competence. The research concludes that most of the teachers at Madrasah Aliyah Sirnamiskin Bandung are following educational standards. However, there are still teachers who use methods in teaching using classical methods and are less proficient in operating available technology and information. The constraints faced related to facilities and infrastructure, in the form of a limited budget, are related to teachers. The strategy of the madrasa head in developing teacher professional competence through discussions, meetings, and question and answer, with a professional approach, can provide a platform and involve teachers in activities held outside the madrasa in developing teacher professional competence.